2008
DOI: 10.1007/s10499-008-9178-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary soybean lecithin on reproductive performance of Chinese mitten crab Eriocheir sinensis (H. Milne-Edwards) Broodstock

Abstract: The effect of increasing levels of dietary phospholipids (PL) on the ovarian development and reproductive performance of Chinese mitten crab Eriocheir sinensis were investigated using four semipurified formulated diets supplemented with 0%, 1.2%, 2.4%, and 3.6% PL. Four groups of 40 females, with an average individual body weight of 95-120 g, were fed the experimental diets for a period of 7 months. Male crabs were introduced into the female rearing system in March, and mating, spawning, and egg hatching occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
3
29
0
1
Order By: Relevance
“…The results of the present study showed that there were significant decrease in the HSI, hepatopancreatic lipid content with concomitant increase in the GSI, ovarian lipid and dry matter content in the process of ovarian development. This is in line with the observations by Cheng et al (1998aCheng et al ( , b, 1999, Wen et al (2001) and Sui et al (2009), reconfirming that the hepatopancreatic lipid reserves are transferred to the developing ovaries during the ovarian maturation of the female E. sinensis. Therefore, it is not surprising that in this study, the dietary HUFA level significantly affected the fatty acid composition (particularly total HUFA content) of the hepatopancreas, ovary, and eggs for all treatments.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study showed that there were significant decrease in the HSI, hepatopancreatic lipid content with concomitant increase in the GSI, ovarian lipid and dry matter content in the process of ovarian development. This is in line with the observations by Cheng et al (1998aCheng et al ( , b, 1999, Wen et al (2001) and Sui et al (2009), reconfirming that the hepatopancreatic lipid reserves are transferred to the developing ovaries during the ovarian maturation of the female E. sinensis. Therefore, it is not surprising that in this study, the dietary HUFA level significantly affected the fatty acid composition (particularly total HUFA content) of the hepatopancreas, ovary, and eggs for all treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been observed for other decapods, including L. vannamei (Palacios, Ibarra & Racotta ), Macrobrachium rosenbergii (Cavalli, Tamtin, Lavens & Sorgeloos ) and E. sinensis (Sui et al . ). The decreased trend of HSI with increasing amounts of GSI confirmed this notion in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Similar results of higher dietary SL resulting in higher GSI have also been observed in Marsupenaeus japonicus (Alava, Kanazawa, Teshima & Sakamoto ) and E. sinensis (Sui et al . ). These results suggest that a diet containing 6.5% fish oil, with no supplemental lecithin, may be sufficient for the growth and survival of C. quadricarinatus adults, and increased amounts of dietary SL may be used to improve ovarian development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diez & Lovrich (2009) hypothesize that the difference recorded in the fecundity is because the primiparous females produced fewer eggs as a result of their smaller size during the adolescent stage. Another factor to consider is the nutritional status, which is strongly related to the production of eggs (Wen et al, 2002;Djunaidah et al, 2003;Sui et al, 2008). Also, a positive relationship was found between the fecundity and CW of mature females.…”
Section: Discussionmentioning
confidence: 99%